Student centered learning: teaching strategies / Noraini Desa, Azimah Jusoh @ Alias & Anis Salwani Abu Bakar - Desa, Noraini; Jusoh @ Alias, Azimah; Abu Bakar, Anis Salwani (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
In education, appropriate teaching method is very important to determine the students’ motivation during teaching and learning process. Student-centered learning is one of the key factors of a memorable educational journey. In this article, we have reviewed about the Student-Centered Learning (SCL) Teaching Strategies that seek to explore the methods, techniques or approaches relevant to student-centered learning. The student-centered learning principle and the contrast between student-centered learning and lecturer-centered teaching will be defined in this study. The methods or techniques discussed from the study of problems or issues related to teaching and learning. In addition, the discussion will focus on appropriate contemporary teaching methods to be applied with the concept of student-centered learning. Among the student-centered learning methods that are meant are cooperative methods, group approaches, discussion techniques, problem solving and project-based learning.